(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
The aimed of this study was to used the partial purified Lipase from the intestinal treat of Carp Fish in treating cooking oil waste in order to reduce averment pollution from it, and to produced fatty acid and glycerol. Cooking oil waste samples were collected from local restaurants in the Kut City, Iraq. The sample treated with the partially purified enzyme at different concentration (0.25, 0.5, 1) % with an enzymatic activity about 100 unit gm for (2, 4, 6) hrs. The concentration of fatty acids for untreated and treated cooking oil with Lipase were determined by high pressure liquid chromatography (HPLC). The physical and chemical properties of cooking oil were studied before lipase treatment Acidity number, density, refractive index, surface tension, impurity percent and viscosity. The result showed highly enzyme activity to hydrolysis ester bond at ph 7 and 40°C for 4 hr for all enzyme concentration and all test.